Computed tomography in intestinal obstruction: a tertiary care perspective from Northern India - Dogra, Varun; Gupta, Shyam; Gilkar, Ishfaq Ahmad; Sandhu, Silvi (International Surgery Journal, 2021)
Background: Intestinal obstruction is a very common surgical emergency faced today in surgical ERs (emergency rooms) all around the globe. With the advent of newer technology, management of intestinal obstruction has changed significantly. Today computed tomography (CT) employs both intravenous as well as oral contrast for determining the cause and the level of obstruction. It also gives additional information regarding any malignancy causing the obstruction, its staging and status of vessels. Thus, a surgeon can go in the procedure with a plan already in mind which can be discussed in detail with experienced surgeons beforehand. Methods: This was a prospective observational study that was done in department of surgery at GMC Jammu over a period of two years. Patients of intestinal obstruction who presented to our department were enrolled in this study. They were subjected to a contrast enhanced CT after due preparation and managed accordingly. Data was recorded in a tabulated fashion and evaluated. Results: After implementing the exclusion criteria’s, a total of 163 patients were included in this study, majority being males in the age group of 20-40 years. Major cause of intestinal obstruction was attributed to post-operative adhesions followed by band obstruction due to various cause. CT findings were seen to be quite significant in evaluation and management of intestinal obstruction. About 30 % of the patients enrolled in our study were treated conservatively while 70 % required operative intervention in form of exploratory laparotomy. Conclusions: Computed tomography is widely available now a days at a cheaper cost. It greatly increases the armamentarium of the surgeon in dealing with this condition. A lot many cases today are dealt conservatively due to high utilisation of CT scan. It also helps the surgeon to preoperatively plan a proper surgical approach